Construction of Aromatic Multilayered Structures Based on the Conformational Properties of N, N'‐Dimethylated Squaramide. Issue 1 (28th January 2021) - Arimura, Maiko; Tanaka, Kimiko; Kanda, Midori; Urushibara, Ko; Fujii, Shinya; Katagiri, Kosuke; Azumaya, Isao; Kagechika, Hiroyuki; Tanatani, Aya
Abstract: Squaramide is a highly rigid four‐membered ring system bearing two carbonyl and two amino groups, and its derivatives have found applications in many fields. We synthesized several N, N' ‐dimethylated oligosquaramides linked via phenyl groups, and investigated their structures in the crystalline state and in solution. Compounds 1, 2 (bissquaramides), and 13 (trissquaramide) exist as folded structures in the crystalline state, in which the aromatic rings are located in a face‐to‐face position. In their multilayered structures, the benzene rings are more nearly parallel and are closer to each other, compared with those in N, N' ‐dimethylated oligoureas. Individual molecules of meta‐ connected compounds 2 and 13 show a helical structure with all‐ R or all‐ S axis chirality, but afford only racemic crystals. The NMR spectra indicated that these compounds retain well‐ordered folded structures in solution. The unique steric and electronic properties of N, N'‐ dimethylated squaramide can provide access to novel functional aromatic multilayered and helical foldamers. Abstract : Fair and square : N, N' ‐dimethylated oligosquaramides linked via phenyl groups exist as folded structures in the crystalline state, in which the aromatic rings are located in a face‐to‐face position. Among them, meta‐ connected compounds show helical structures with all‐ R or all‐ S axis chirality. These compounds exist in the well‐ordered folded structures in solution. The cis conformational preference of aromatic N, N'‐ dimethylated squaramides is thus useful in the construction of aromatic multilayered and helical foldamers.